2021
DOI: 10.3390/f12030290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Disturbance on the Activity of Medium–Large Mammals in Myanmar Tropical Forests

Abstract: The effects of human disturbance represent one of the major threats for wildlife conservation. Many studies have shown that wildlife avoids or reduces direct contact with human activities through changes in activity patterns, and by minimizing spatiotemporal overlap. In this study, we investigated the possible effects of human presence on the temporal activity of medium-to-large mammals using two areas in Myanmar that differ in the intensity of human disturbance. We monitored temporal segregation mechanisms us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 74 publications
(77 reference statements)
3
16
1
Order By: Relevance
“…A separate consideration concerns humans, whose presence was recorded by a considerably higher number of detections in the RYER (3109) compared to the HWS (96), with significantly higher occurrence and detectability values. This fact confirmed that the RYER is more disturbed, dealing with not only "chronic" disturbance effects like habitat degradation and fragmentation but also "acute" disturbance conditions due to the high rate of human presence in the forests that can affect species in many ways, as documented for this area with a significant effect on some species activity patterns [25]. As we said previously, we are aware that the two areas were distant from each other, meaning that some community patterns could be related to differences in geographical and landscape features and not only to human disturbances.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…A separate consideration concerns humans, whose presence was recorded by a considerably higher number of detections in the RYER (3109) compared to the HWS (96), with significantly higher occurrence and detectability values. This fact confirmed that the RYER is more disturbed, dealing with not only "chronic" disturbance effects like habitat degradation and fragmentation but also "acute" disturbance conditions due to the high rate of human presence in the forests that can affect species in many ways, as documented for this area with a significant effect on some species activity patterns [25]. As we said previously, we are aware that the two areas were distant from each other, meaning that some community patterns could be related to differences in geographical and landscape features and not only to human disturbances.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we analyzed the status of two mammal communities in two geographically distinct areas in Myanmar that are similar in climate, elevation, and habitat types but have sharp differences in their levels of habitat degradation and human disturbance. We used camera trap data to evaluate both biodiversity levels (estimated species richness) and some ecosystem functions such as trophic niches and body mass in two different contexts: a well-preserved and mostly untouched evergreen forest and a degraded and fragmented forest with a high level of human pressure [25]. It is important to increase our knowledge of the status of communities and species because no previous studies, with a structured monitoring scheme, have been done in these study areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proclivity for exploratorytype activities (e.g., foraging) during the daylight hours was somewhat unexpected, though the exploratory behavioral state featured low movement potentially allowing individuals to remain active and undetected. Other studies reported diurnal activity in wild pigs, particularly in areas where animals are less likely to experience disturbance (Keuling et al 2008a, Podgórski et al 2013, Cremonesi et al 2021). Our study area was primarily forested with substantial understory cover, potentially limiting human disturbances and providing enough concealment to facilitate modest diurnal activity.…”
Section: Discussionmentioning
confidence: 98%